Seed coat sculpture of subgenus Ceratotropis (Piper) verdc., genus Vigna Savi in India and its taxonomic implications. Issue 1 (2nd January 2017) - Umdale, Suraj D.; Patil, Pravin D.; Malik, Surendra K.; Latha, M.; Rao, Satyawada R.; Yadav, Shrirang R.; Gaikwad, Nikhil B.; Bhat, Kangila V.
Abstract: The seed coat morphology was studied using scanning electron microscopy in 21 species (of which two are both cultivated and wild) of subgenus Ceratotropis (Piper) Verdc. and one species each from subgenus Plectotropis and subgenus Vigna of genus Vigna . The macromorphological and micromorphological seed characters, which include seed shape, testa texture, hilum, aril, testa pattern and ornamentation of periclinal wall, exhibited well-defined variability among the studied taxa. The smallest seeds were recognized in Vigna subramaniana (1.97 × 1.91 mm) and the largest in Vigna unguiculata (7.02 × 4.45 mm). The smallest hilum was observed in Vigna subramaniana (0.50 ± 0.01 mm) and the largest in Vigna umbellata (3.57 ± 0.05 mm). Novel morphological features such as reticulate, reticulate-foveate, alveolate, colliculate-pusticulate, substriate, ruminate-reticulate and ruminate-channelled reticulations of periclinal wall of the testa cell and hilum structure were observed in addition to those reported in earlier studies. In the present investigation, we reported the seed micromorphology of wild endemic Vigna species, namely Vigna sahyadriana, Vigna subramaniana, Vigna hainiana, Vigna indica, Vigna khandalensis and Vigna konkanensis for the first time. Based on seed characters, the taxonomic identity and species complex in the subgenus Ceratotropis has been discussed. A key to the species has been developed based on seed characters.